Court of Four Seasons (Pacific Novelty Co.)
On verso: Designed by Henry Bacon, New York. This is the West Central Court and one of the most beautiful sections of the Exposition. It is said that Hadrians Villa, one of the historic Roman Palaces, is the inspiration for this court.